PERAN PETUGAS KESEHATAN DAN PEMERINTAH DESA TERHADAP PERUBAHAN PHBS SELAMA PANDEMI COVID-19 - Ahdatul Islamiah; Sri Mega Ayu (Poltekkes Kemenkes Surabaya, 2023)
Indonesia is being hit by an outbreak of the Covid-19 virus which attacks therespiratory tract and the process of transmission can be through activities without paying attention to clean and healthy lifestyle (PHBS), for example not wearing a mask, not washing your hands, not keeping your distance because the transmission can be through fluids coming from the nose and mouth. Meanwhile, health workers and village government are elements that can support achieving optimal PHBS in the community, especially during the Covid-19 pandemic. Thus, this study aims to identify the relationship between the roles of health workers and village government towards changes in community PHBS during the COVID-19 pandemic.This type of research is quantitative research with an internal statistical research design through a cross sectional approach. A sample of 75 respondents obtained through purposive sampling technique. The Independent Variable is the role of health workers and the village government, while the Dependent Variable is the change in community PHBS. The data analysis used is the Chi Square test.The results showed that there was a relationship between the role of health workers and changes in community PHBS during the Covid-19 pandemic with a p value (0.022) <(0.050). Likewise, the role of the village government also has a relationship with changes in community PHBS during the Covid-19 pandemic with a p value (0.039) < (0.050).The positive role of health workers and village government has been shown to have a relationship with changes in community PHBS during the Covid-19 pandemic, so it is recommended for health workers to maintain the quality of service to the community, especially in providing health education about PHBS in household settings. The village government is advised to continue to approach the community and work with health workers in an effort to provide information about the importance of implementing PHBS, especially during the Covid-19 pandemic.